1995
DOI: 10.1007/bf00193727
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration of grapevine (Vitis sp.) protoplasts isolated from embryogenic tissue

Abstract: Protoplasts with high embryogenic competence could be isolated from leaf-disk-derived embryos and embryoids of Vitis sp. cv. Seyval blanc. After a 4-week induction treatment in NN-69 medium supplemented with 4.0mg/l naphthoxyacetic acid (NOA) and 0.9mg/l thidiazuron (TDZ) and subsequent subcultivation in hormone-free medium, 38.5% of the developed microcalluses showed somatic embryogenesis. In contrast, only few formed somatic embryos after induction in CPW-13 medium with either 1.0mg/l 2,4-dichlorophenoxyacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…Most recently, protoplasts underwent somatic embryogenesis and regenerated plants; this was possible only when protoplasts were isolated from leaf-derived embryogenic callus or embryos (Reustle et al, 1995;Zhu, et aI., 1997). Additionally, tendrils were proposed as an alternative explant (Salunkhe et aI., 1997).…”
Section: Induction and Culture Of Embryogenic Callusmentioning
confidence: 98%
“…Most recently, protoplasts underwent somatic embryogenesis and regenerated plants; this was possible only when protoplasts were isolated from leaf-derived embryogenic callus or embryos (Reustle et al, 1995;Zhu, et aI., 1997). Additionally, tendrils were proposed as an alternative explant (Salunkhe et aI., 1997).…”
Section: Induction and Culture Of Embryogenic Callusmentioning
confidence: 98%
“…Results of another work on grape cv. 'Seyval-Blanc', the NN medium with 4 mg /l NOA and 0.9 mg/l TDZ showed the highest percentage of embryogenic callus production (Reustle et al 1995). Results of present study revealed that, applied hormonal treatments (IAA 2 mg/l and BAP 5 mg/l) were very effective in embryogenesis in 'Red-Sultanina' and 'Flame-Seedless'.…”
Section: Resultsmentioning
confidence: 53%
“…Because both auxins and cytokinins can affect adventitious embryogenesis from cultured grape explants (Reustle et al, 1994;Perl et al, 1995, Torregrosa et al, 1995Nakano et al, 1997), we investigated their effects on callus induction in MS media. In our stem explant cultures, calli were induced and developed regardless of the kind of auxin present in the medium, whereas the potential for callus induction in our leaf cultures depended on a specific auxin Figure 6.…”
Section: Discussionmentioning
confidence: 99%